2016
DOI: 10.1017/s1366728916000614
|View full text |Cite
|
Sign up to set email alerts
|

A role for putamen in phonological processing in children

Abstract: Bilingual children are required to successfully develop phonological skills in two languages, yet little is known about the neural correlates associated with them. We obtained structural imaging data from 30 Hindi–English children aged between 8 and 10 years and used voxel based morphometry to explore neuroanatomical correlates of behavioural measures of phonological awareness. Our results showed that phonological skills in English are predicted by grey matter volume of bilateral putamen, but solely by right p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, the laterality of these effects varied, with increases reported in the right 19 , left 25 , and bilateral putamen 24 . Part of the differences with respect to the laterality of the observed effects might stem from variability in phonological transparency of languages the bilingual used, which has been shown to play a role in a previous study 42 . Phonological skills in Hindi, a phonologically transparent language, have been predicted by larger volumes of the right putamen, whereas performance on the same task in English, a relatively phonologically non-transparent language, was linked to larger volumes of the bilateral putamen 42 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the laterality of these effects varied, with increases reported in the right 19 , left 25 , and bilateral putamen 24 . Part of the differences with respect to the laterality of the observed effects might stem from variability in phonological transparency of languages the bilingual used, which has been shown to play a role in a previous study 42 . Phonological skills in Hindi, a phonologically transparent language, have been predicted by larger volumes of the right putamen, whereas performance on the same task in English, a relatively phonologically non-transparent language, was linked to larger volumes of the bilateral putamen 42 .…”
Section: Discussionmentioning
confidence: 88%
“…Part of the differences with respect to the laterality of the observed effects might stem from variability in phonological transparency of languages the bilingual used, which has been shown to play a role in a previous study 42 . Phonological skills in Hindi, a phonologically transparent language, have been predicted by larger volumes of the right putamen, whereas performance on the same task in English, a relatively phonologically non-transparent language, was linked to larger volumes of the bilateral putamen 42 . These results were interpreted as indication that phonological skills in a non-transparent language require support from both hemispheric parts of this structure.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, left putaminal damage has been associated with foreign accent syndrome (Berthier et al., ). And finally, a recent study found that children with poor phonological skills in the L1 and L2 have less gray matter density in the putamen, bilaterally (Cherodah, Rao, Midha, & Sumathi, ). All this evidence points to the putamen as an area necessary for optimal language processing.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the putamen is associated with phonological processing and articulation [ 166 , 167 ], the bilingual advantages for language learning may be connected to the effects of language experience on speech processing, in addition to cognitive control. Consistent with this notion, Kaushanskaya and Marian [ 157 ] found that bilinguals outperformed monolinguals when learning novel words, and that better performance was correlated with phonological working memory among early bilinguals, but not late bilinguals or monolinguals.…”
Section: Language Learningmentioning
confidence: 99%